Menilai Kualitas Tugas Matematika Buatan Guru SMP dengan Stimulus Soal Berbasis Literasi dan Numerasi yang Menumbuhkan Berpikir Kritis Siswa - Ismail; Tatag Yuli Eko Siswono; Masriyah; Abadi (MATHEdunesa, 2026)
Questions that encourage students to construct meaning and build mental connections tend to foster critical thinking skills. Previous research on junior high school mathematics teachers shows that, in reality, teachers often have not been successful in teaching students to think critically; instead, they focus more on teaching the subject matter content alone. The problem concerns how to improve the quality of mathematics tasks designed by junior high school mathematics teachers in Pasuruan Regency, and whether the tasks developed by teachers have already fostered students’ critical thinking skills. One effort that teachers can undertake is to use literacy- and numeracy-based problem stimuli in the tasks given to students. However, the development of literacy- and numeracy-based questions that can enhance critical thinking skills has not yet been well mastered by mathematics teachers. Therefore, they need to engage in direct, interactive activities with experts in mathematics education, particularly in the field of critical thinking. Through the workshop on critical thinking–oriented learning for junior high school mathematics teachers in Pasuruan Regency, it is expected that teachers will be able to design literacy- and numeracy-based problem stimuli to be used in critical thinking–oriented mathematics instruction at the junior high school level. The results of the teacher mentoring activities in designing mathematics tasks with literacy- and numeracy-based problem stimuli for critical thinking–oriented mathematics learning at the junior high school level are as follows: 16 out of 19 participants (84%) produced stimuli that were well designed based on literacy and numeracy, containing sufficient information to develop questions that trigger students’ critical thinking skills; 2 out of 19 participants (10.5%) produced stimuli that were fairly well designed based on literacy and numeracy, containing limited information to develop questions that stimulate students’ critical thinking skills; and 1 out of 19 participants (5%) produced stimuli that were poorly designed based on literacy and numeracy, containing no information that could develop questions to stimulate students’ critical thinking skills. Based on the questionnaire results, 53.8% of participants strongly agreed and 46.2% agreed that the workshop materials could be easily understood and applied; 76.9% strongly agreed and 23.1% agreed that the workshop materials were delivered in a well-structured and systematic manner; 84.8% strongly agreed and 15.4% agreed that the resource person mastered the material presented; 61.5% strongly agreed and 38.5% agreed that the resource person presented the material clearly and sequentially; 69.2% strongly agreed and 30.8% agreed that the answers provided by the resource person to participants’ questions were very clear; and 38.5% strongly agreed, 46.2% agreed, while only 15.4% disagreed that the duration of the training was appropriate.